Selected English-Language Bibliography of Interest for Hungarian Cultural Studies: 2019-2020 - Zsuzsanna Varga (Hungarian Cultural Studies, 2020)
As the above title indicates, because of the publication schedule of Hungarian Cultural Studies this bibliography straddles 2019-2020, covering the period since the publication in Fall of 2019 of last year’s bibliography in this journal. Each year’s bibliography may also be supplemented by earlier items, which were retrieved onlyrecently. Although this bibliography series can only concentrate on English-language items, occasional items of particular interest in other languages may be included. For a more extensive bibliography of Hungarian Studies from about 2000 to 2010, for which this is a continuing update, see Louise O. Vasvári, Steven Tötösy de Zepetnek, and Carlo Salzani. “Bibliography for Work in Hungarian Studies as Comparative Central European Studies.” CLCWeb: Comparative Literature and Culture (Library) (2011): http://docs.lib.purdue.edu/clcweblibrary/hungarianstudiesbibliography